The nabi-rasul in Arabian/semitic religious tradition: Qur’anic monotheism, Prophet Muhammad and the shaping of Muslim world view - Yusuf, Imtiyaz (Islamic Research Institute, Islamabad, Pakistan, 2019)
As the carriers of the message and practice of monotheism defined differently in Judaism, Christianity, and Islam, the nabi and rasul translated as prophets occupy a central position in the Arabian/Semitic history of religion and its geographic space. This paper is based on the theory of history of religions. It views Arabia—the expanded geographic land space between Mesopotamia, Palestine, and Arabian Peninsula, which is the home ground of the religious contest between monotheism and polytheism—as a religious territory and not as a map. The contest between monotheism and polytheism in Arabia lies at the heart of religious, social, and economic disorder, chaos, and injustice, which obstructs the sustenance of equality, justice, and fraternity based on monotheism. The paper focuses on the religious role of Muhammad (peace be upon him) as a post-Judeo-Christian prophet in Arabia by expounding on the meaning of revelation in Islam as being a scripture and the role of Prophet Muhammad as a human exemplar. The last part of this paper explores the humanness of Prophet Muhammad and the divineness of an unseen, imageless Allah—two religious dimensions of the Qur’anic world view, which shape the daily life of a Muslim as an individual, his/her piety, and social engagement—representing life and thought.